Vacuolar occupancy is crucial for cell elongation and growth regardless of the underlying mechanism. (3rd August 2021) - Kaiser, Sabrina; Eisele, Sophie; Scheuring, David
ABSTRACT: In the physiological range, the phytohormone auxin inhibits the growth of underground tissues. In the roots of Arabidopsis thaliana, cell size inhibition has been shown to be accompanied by auxin-mediated reduction of vacuole size. A tonoplast-localized protein family (Networked 4) with actin-binding capacity was demonstrated to modulate the compactness of the vacuole. Overexpression of NET4A led to smaller, more spherical and compact vacuoles, which occupied less cellular space compared to wild type. This reduction of vacuolar occupancy is similar to the observed auxin-induced decrease in occupancy, albeit there are enormous morphological differences. Here, we show that a net4a net4b double mutant and a NET4A overexpressor line are still sensitive to auxin-induced vacuolar constrictions. However, the overexpressor showed a partial auxin resistance accompanied by more compact vacuoles, thereby indicating an additional regulatory mechanism. Furthermore, we show that other NET superfamily members do not compensate for the loss of NET4A and NET4B expression on the transcriptional level. This leads us to hypothesize that regulation of vacuole size is a general mechanism to regulate cell expansion and that other players besides NET4 must participate in regulating the vacuole–cytoskeleton interface.